Demographics, psychiatric comorbidities, and hospital outcomes across eating disorder types in adolescents and youth: insights from US hospitals data - Jaka, Sanobar; Pokhrel, Sandesh; Patel, Archna; Sejdiu, Albulena; Taneja, Sanjana; Vashist, Sreshatha; Arisoyin, Abimbola; Bachu, Anil K.; Rajaram Manoharan, Senthil Vel Rajan; Mogallapu, Raja; Patel, Rikinkumar S. (Frontiers in Child and Adolescent Psychiatry, 2024)
Objective: Our study aims to delineate the differences in demographics, comorbidities, and hospital outcomes by eating disorder types in adolescents and transitional-age-youth (TAY) (15 -26 years); and measure the association with psychiatric comorbidities.Methods: We conducted a cross-sectional study using the nationwide inpatient sample (NIS 2018-2019) and included 7,435 inpatients (age 12-24) with a primary diagnosis of eating disorders: anorexia nervosa (AN, 71.7%), bulimia nervosa (BN, 4.7%), avoidant/restrictive food intake disorder (ARFID, 9.5%), and other. We used independent logistic regression models controlled for demographics to evaluate the adjusted odds ratio (aOR) association of comorbidities with eating disorder types.Results: The mean age of BN inpatients was 17.5 years which was significantly higher compared to total inpatients with eating disorders (15.9 years). About four-fifths of the inpatients with AN and BN were females whereas ARFID was seen in a higher proportion of males (32.6% vs. 13.7% overall). Anxiety (57.5%) and depressive (47.3%) disorders were prevalent in total inpatients with eating disorders with suicidal behaviors seen significantly higher in BN (25.7% vs. 12.9% overall). The likelihood of OCD was higher in all eating disorder types i.e., AN (OR 2.14), BN (OR 1.79) and ARFID (OR 1.74) but, anxiety (OR 1.52) and neurodevelopmental (OR 1.70) disorders were significantly higher in ARFID. In terms of hospital outcomes, inpatients with ARFID had a longer mean length of stay (13.7 days vs. 8.4 days in BN) and higher mean total charges ($87,747 vs. $44,882 in BN).inpatients diagnosed with Anorexia Nervosa (AN), Bulimia Nervosa (BN), and Avoidant/Restrictive Food Intake Disorder (ARFID). Specifically, BN inpatients, belonging to older age brackets, manifest elevated occurrences of depressive disorders and suicidal tendencies. ARFID is linked to prolonged hospitalization and increased costs, underscoring distinctive complexities in care. This highlights the significance of personalized interventions that account for demographic variations and psychiatric comorbidities, aiming to improve outcomes for diverse populations affected by eating disorders.